An analytical review for the power system of a spacecraft - CHATURVEDI, Sudhir Kumar CHATURVEDI (INCAS bulletin, 2022)
Electrical bus is needed for the operation of all active spacecraft systems and subsystems. In the spacecraft mechanism, the battery charging system and the bus storage continued with bus control, the conditioning and bus distribution is an essential part for keeping the spacecraft in working mode. In this paper, the discussion for electrical power system (EPS) analysis in the spacecraft body will be elaborated from the previous research papers on this subject covering the topics of solar array, solar array drive, over current and over voltage protection, battery charging and discharging, bus control, conversion.